Aesthetics of Benedetto Croce as an Alternative to Modernist Notion of Aesthetics - Daraškevičiūtė, Vaiva (Religija ir kultūra, 2011)
This article analyzes the aesthetics of Benedetto Croce as an alternative to modernistic notion of aesthetics. Croce contradicts empiricism and rationalism proposing the opinion that the process of perception begins not at the level of intelligence or senses, but at the level of intuition at first. The discussion on Croce’s intuition conception helps us to demonstrate that the art in his aesthetics is perceived more in terms of philosophy of art than in terms of modernistic aesthetics. That is shown in two steps: firstly, discussing how important in Croce’s philosophical system is intuition itself as the primary perception; secondly, showing that intuition for Croce is possible only as expression and it means that in this way perception is always creative and active relationship with the world.